2019
DOI: 10.1186/s12874-019-0801-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between influenza vaccination and socioeconomic status in high income countries varies by the measure used: a systematic review

Abstract: Background The purpose of this paper is to systematically review the literature on the relationship between socioeconomic status (SES) and influenza immunization and to examine how certain measures of SES may influence interpretations of this relationship. Methods We conducted a systematic review of existing peer-reviewed literature to evaluate the above relationship in the general population. Electronic databases (MEDLINE and EMBASE) were searched from January 2012 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 47 publications
4
54
1
3
Order By: Relevance
“…A recent systematic review by Vukovic et al [ 77 ] revealed that individuals living in the most deprived areas had a lower influenza vaccination coverage, while the association between socio-economic indices and coverage was contrasting. Similar results have been obtained by another systematic review [ 78 ] which highlighted that this association may depend on the measures used to assess and define socio-economic status.…”
Section: Discussionsupporting
confidence: 88%
“…A recent systematic review by Vukovic et al [ 77 ] revealed that individuals living in the most deprived areas had a lower influenza vaccination coverage, while the association between socio-economic indices and coverage was contrasting. Similar results have been obtained by another systematic review [ 78 ] which highlighted that this association may depend on the measures used to assess and define socio-economic status.…”
Section: Discussionsupporting
confidence: 88%
“…with education, socioeconomic status and employments as the main associated factors. A systematic review written by Kelsey reported that higher levels of socio economic status resulted in higher levels of influenza vaccination; 4.5% reported a negative association; and 14.3% found no association (Lucyk et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This result could reflect vaccination-seeking behavior being higher in areas where influenza rates are typically high thus increasing disease risk perception [40]. Additionally, some prior studies have shown mixed results regarding the relationship between socioeconomic status and influenza vaccination, and that these differing results may relate to the way that socioeconomic status is defined, or what location the study takes place in [41, 42]. Lastly, this may be a result of the source of our vaccination data, which has low coverage in some areas and may suffer from its own measurement biases, which highlights the need for more data on influenza vaccine uptake and the characteristics of those who vaccinate.…”
Section: Resultsmentioning
confidence: 99%